COMPARISON OF MERISTIC CHARACTERISTICS OF Barbodes schwanefeldii LIVING AROUND THE FLOATING NET CAGE AREA AND IN THE AREA WITH NO FLOATING NET CAGE IN THE KOTO PANJANG DAM RIAU PROVINCE - Sari, Desi Maya; Putra, Ridwan Manda; Windarti, Windarti (Asian Journal of Aquatic Sciences, 2022)
Barbodes schwanefeldii or kapiek fish is a type of freshwater fish that lives around the floating net cage area and in the area with no floating net cage in the Koto Panjang Dam. This study aims to determine the meristical characteristics of B. schwanefeldii living in that dam, especially around the floating net cage area and in the area with no floating net cage. This study was conducted in October-November 2021. Sampling was done 1 time, the number of fish collected was 68 fishes that were caught around floating net cage and 23 fishes that were caught in the area with no floating net cage. A total of 11 meristical characteristics were calculated and studied. Results shown that there were no significant morphological and meristical different of the fish living in the area with cage or in the area with no floating net cage. The the meristical characteristics were as follows: D III.8, P I.14, V I.8, A I.5, C 18. The number of scales in front of the dorsal fin was 13 scales, around the body was 28-30, around the caudal peduncle was 18, in the linea lateralis was 34-36, above linea lateralis was 8 and below linea lateralis was 4.